A Parametric Study of the Impact of the Cooling Water Site Specific Conditions on the Efficiency of a Pressurized Water Reactor Nuclear Power Plant. (27th August 2014) - Ibrahim, Mohamed M. A.; Badawy, Mohamed R.
Abstract : In this study, the thermal analysis for the impact of the cooling seawater site specific conditions on the thermal efficiency of a conceptual pressurized water reactor nuclear power plant (PWR NPP) is presented. The PWR NPP thermal performance depends upon the heat transfer analysis of steam surface condenser accounting for the key parameters such as the cooling seawater salinity and temperature that affect the condenser overall heat transfer coefficient and fouling factor. The study has two aspects: the first one is the impact of the temperature and salinity within a range of (290 K–310 K and 0.00–60000 ppm) on the seawater thermophysical properties such as density, specific heat, viscosity, and thermal conductivity that reflect a reduction in the condenser overall heat transfer coefficient from 2.25 kW/m 2 K to 1.265 kW/m 2 K at temperature and salinity of 290 K and 0.00 ppm and also from 2.35 kW/m 2 K to 1.365 kW/m 2 K at temperature and salinity of 310 K and 60000 ppm, whereas the second aspect is the fouling factor variations due to the seawater salinity. The analysis showed that the two aspects have a significant impact on the computation of the condenser overall heat transfer coefficient, whereas the increase of seawater salinity leads to a reduction in the condenser overall heat transfer coefficient.